Ultralow lattice thermal conductivity induced high thermoelectric performance in the δ-Cu2S monolayer. Issue 21 (17th May 2019) - Yu, Jiabing; Li, Tingwei; Nie, Ge; Zhang, Bo-Ping; Sun, Qiang
Abstract : The δ-Cu2 S monolayer exhibits an ultralow κ 1 of 0.10 W m −1 K −1 and a high ZT of 1.33 at 800 K. Abstract : Motivated by the recent experimental exfoliation of β-Cu2 S thin films and the theoretical finding of a new phase labeled the δ-Cu2 S monolayer, we carried out extensive studies on thermal conductivity and thermoelectric properties of the new phase using first principles combined with Boltzmann transport theory, focusing on the analysis of group velocities, Gruneisen parameters, three-phonon scattering rates, and the scattering phase space. Our results show that the δ-Cu2 S monolayer exhibits an intrinsically ultralow lattice thermal conductivity of 0.10 W m −1 K −1 at 800 K. Such an ultralow lattice thermal conductivity leads to a high thermoelectric figure of merit ZT = 1.33 at 800 K in an optimum p-type doping concentration, which is not only larger than the value of 1.23 in In2 S3 doped Cu2 S at 850 K but also comparable with the value of 1.7 in Cu1.97 S at 1000 K, exhibiting good potential in thermoelectric applications.